DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH SISWA MENGGUNAKAN LANGKAH POLYA MATERI PECAHAN BERDASARKAN GENDER - Rusmala, Rusmala; Nanna, A. Wilda Indra; Bua, Agustinus Toding (Universitas Borneo Tarakan, 2023)
This study aims to describe elementary school students' fractional problem solving abilities based on gender. This type of research uses descriptive qualitative research. Data collection techniques include tests and interviews. Based on the research results, it was found that there were differences in problem solving abilities between male and female students, where male students tended to solve problems completely. Male students are more dominant than female students, especially in problem solving and rechecking steps. Male students fulfilled 4 steps of Polya problem solving correctly, and female students were only able to fulfill 2 of the 4 steps correctly